Distance from a distance: the robustness of psychological distance effects - Trautmann, Stefan T. (Theory and decision, 2019)
Psychological distance effects have attracted the attention of behavioral economists in the context of descriptive modeling and behavioral policy. Indeed, psychological distance effects have been shown for an increasing number of domains and applications relevant to economic decision-making. The current paper questions whether these effects are robust enough for economists to apply them to relevant policy questions. We demonstrate systematic replication failures for the distance-from-a-distance effect shown by Maglio et al. (J Exp Psychol Gen 142:644-657, 2013), and relate them to theoretical arguments suggesting that psychological distance theories are currently too poorly specified to make predictions that are precise enough for economic analyses.
Gesehen am 29.11.2019